Disclosure Within Shopping Apps-Mobile Based: Usage Determination Factors - Yulandri, Elsa; Hurriyati, Ratih; Dirgantari, Puspo Dewi (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
Although Indonesia is recorded as the third-largest country in terms of mobile shopping application installations globally, the level of mobile shopping activity remains low. This study employs a quantitative research design to analyze the roles of personalization, direct marketing, and hedonic value in shaping behavioral intentions and their impact on the usage behavior of mobile shopping applications. Data were collected through a survey using a purposive sampling technique, involving 282 Gen Z respondents in Indonesia. The questionnaire underwent measurement model testing through Outer Loading, Construct Reliability and Validity, and Discriminant Validity to ensure reliable results, followed by hypothesis testing using SEM-PLS data analysis techniques. The analysis reveals that direct marketing, personalization, and hedonic value have a significant direct influence on behavioral intentions, explaining 93.2% of the variance. Additionally, behavioral intention is found to directly affect usage behavior, although this model accounts for only 37.4% of the variance. Most importantly, behavioral intention mediates the influence of direct marketing, personalization, and hedonic value on usage behavior. These findings suggest that personalization, direct marketing, and hedonic value are crucial factors in fostering behavioral intentions among Gen Z in Indonesia, thereby enhancing the usage of mobile shopping applications.